DEVELOPING AUDIO-VISUAL LEARNING MEDIA IN THE COMPETENCY OF MAKING ROBE PATTERNS BASED ON THE DESIGN (Journal of Vocational and Career Education, 2022)
The videos for making fashion patterns taken by teachers from YouTube only fulfilled some indicators in making pattern subjects. It was caused by time limitations in creating audiovisuals by the teacher. Furthermore, some teachers also did not master IT especially in making audio-visual media. The students faced difficulty in understanding making robe patterns based on the design without the teacher’s guidance when the teacher used the lecture method, job sheet, and module. The purposes were (1) to examine the audio-visual learning media in the competency of making robe patterns based on the design. (2) to examine the effectiveness of learning media and (3) to examine the practicality of it in the competency of making robe patterns based on the design. The research model applied ADDIE. The result showed the audio-visual learning media was proved feasible by material and media experts where The CVR achieved more than 0,75. Audio-visual learning media was effective in the learning process since it showed an improvement in learning outcomes. The results of the t-test with a significance of 0 and the N-gain test results of 53.60%. This media was very practical in making robe patterns with a percentage gained 89.58% from students’ users and 94.92% from teachers.